2004
DOI: 10.1128/jb.186.24.8499-8507.2004
|View full text |Cite
|
Sign up to set email alerts
|

RpoS-Regulated Genes ofEscherichia coliIdentified by RandomlacZFusion Mutagenesis

Abstract: RpoS is a conserved alternative sigma factor that regulates the expression of many stress response genes in Escherichia coli. The RpoS regulon is large but has not yet been completely characterized. In this study, we report the identification of over 100 RpoS-dependent fusions in a genetic screen based on the differential expression of an operon-lacZ fusion bank in rpoS mutant and wild-type backgrounds. Forty-eight independent gene fusions were identified, including several in well-characterized RpoS-regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
90
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 92 publications
2
90
1
Order By: Relevance
“…ROS have been previously implicated in programmed cell death in eukaryotes (21,29), including in yeast (12,17), in the life span of several organisms (25,33), in the senescence of bacteria (6), and in the mode of action of some antibiotics (13)(14)(15). It was previously reported that the stationary-phase sigma factor S , encoded by rpoS (16,19), positively regulates the formation of catalase and is responsible for the elevated levels of this enzyme during stationary growth phase (24,34,35). Since catalase detoxifies ROS, we asked whether resistance of stationary-phase cells to mazEF-mediated cell death was caused by the elevated levels of catalase produced at that time.…”
mentioning
confidence: 99%
“…ROS have been previously implicated in programmed cell death in eukaryotes (21,29), including in yeast (12,17), in the life span of several organisms (25,33), in the senescence of bacteria (6), and in the mode of action of some antibiotics (13)(14)(15). It was previously reported that the stationary-phase sigma factor S , encoded by rpoS (16,19), positively regulates the formation of catalase and is responsible for the elevated levels of this enzyme during stationary growth phase (24,34,35). Since catalase detoxifies ROS, we asked whether resistance of stationary-phase cells to mazEF-mediated cell death was caused by the elevated levels of catalase produced at that time.…”
mentioning
confidence: 99%
“…The oxidative stress response controlled by RpoS in stationary phase is well studied, and a number of proteins that metabolize reactive oxygen species, such as catalase and superoxide dismutase, are under regulation of S (25,26). Our demonstration of sensitivity of rpoS mutants to the replication inhibitor AZT during exponential growth suggests that S may control other functions important for DNA damage repair or tolerance.…”
Section: How Does Rpos Promote Dna Damage Survival?mentioning
confidence: 87%
“…RpoS regulates over 100 genes during stationary phase and up to 500 genes in response to various other stresses (54,68,71). In addition, RpoS has been found by transcription microarray analysis to regulate directly or indirectly almost 300 genes in exponential-phase cells (14a).…”
mentioning
confidence: 99%